Network security bible - Cole, Eric (Wiley Pub., 2009)
"Network security is constantly evolving, and this comprehensive guide has been thoroughly updated to cover the newest developments. If you are responsible for network security, this is the reference you need at your side. Covering new techniques, technology, and methods for approaching security, it also examines new trends and best practices being used by many organizations. The revised Network Security Bible complements the Cisco Academy course instruction in networking security"--Resource description page.
Print version record
Keywords: Computer security; Computer networks -- Security measures; Sécurité informatique; Réseaux d'ordinateurs; Sécurité; Mesures; Computer networks; Security measures